The Expression of Matrix Metalloproteinase-12 by Oligodendrocytes Regulates Their Maturation and Morphological Differentiation - Larsen, Peter H. (J Neurosci, 2004)
Matrix metalloproteinases (MMPs) have important roles in many processes of the developing CNS requiring proteolytic activity such as the migration of neuronal precursors, axonal outgrowth, and vascularization. Another developmental event involving proteolysis is myelin formation, whereby the extensive processes elaborated from oligodendrocytes (OLs) enwrap axons. Here we find MMP-12 transcripts to be produced by OLs in much higher levels than other MMP members examined. MMP-12 activity correlated with the ability of OLs to extend processes in vitro, suggesting a role for MMP-12 in the morphological differentiation of OLs. This was corroborated by results that OL lineage cells from MMP-12 null mice were retarded in their ability to differentiate morphologically and that this deficiency was overcome by the exogenous addition of active MMP-12. Finally, the maturation of oligodendrocyte precursor cells (OPCs) to OLs was significantly reduced in cultures from MMP-12 null mice compared with wild-type controls. We conclude that OL lineage cells express MMP-12 during their maturation and that MMP-12 activity has functional involvement both in maturation of OPCs and in the ability of OPCs and OLs to extend processes.